2021
DOI: 10.3390/cryst11070731
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Water Reducing Agents on Early Hydration Property of Ferrite Aluminate Cement Paste

Abstract: The ferrite aluminate cement (FAC) could rapidly lose fluidity or workability due to its excessive hydration rate, and greatly reduce the construction performance. Chemical admixtures are commonly used to provide the workability of cement-based materials. In this study, to ensure required fluidity of FAC, chemically different water reducing agents are incorporated into the FAC pastes. The experiments are performed with aliphatic water reducing agent (AP), polycarboxylic acid water reducing agent (PC) and melam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…The appearance of this phenomenon could be explained by the following point of view. The addition of PCEs reduced the degree of agglomeration of cement particles and increased the quantity of cement particles participating in the hydration reaction through charge repulsion and steric hindrance, resulting in a higher hydration temperature peak [33]. The degree of temperature increase of cement paste with Type B and C was slightly higher than that cement paste with Type A.…”
Section: Fig 8 Adsorption Amount Of Pces With Different Dosagementioning
confidence: 94%
“…The appearance of this phenomenon could be explained by the following point of view. The addition of PCEs reduced the degree of agglomeration of cement particles and increased the quantity of cement particles participating in the hydration reaction through charge repulsion and steric hindrance, resulting in a higher hydration temperature peak [33]. The degree of temperature increase of cement paste with Type B and C was slightly higher than that cement paste with Type A.…”
Section: Fig 8 Adsorption Amount Of Pces With Different Dosagementioning
confidence: 94%
“…Although the CSC has the increasing performance advantages, its large-scale application is limited resulting from the scarcity of alumina raw materials (Huang et al, 2020), for which the use of ferrite materials to partially replace aluminum materials in calcium sulphate aluminate cement to make ferrite aluminate cement (FAC) an attempt to solve this problem (Bullerjahn et al, 2014). Huang et al (2021) investigated the effects of the superplasticizers on workability of FAC pastes. As the experimental study showed, in the FAC pastes with W/C of 0.29, when the fluidity was 180 mm, 240 mm and 270 mm, the required dosage of polycarboxylate acid-based water reducing agent (PC) was lower than that of the melamine-based water reducing agent (MA) and aliphatic-based water reducing agent (AP), which indicated that the PC had slow setting effect and better dispersion capacity in comparison.…”
Section: Calcium Sulfoaluminate Cement Concrete and Ferrite Aluminate...mentioning
confidence: 99%